Secondary Glomerulonephritis With Peripheral Arterial Disease Due To Systemic Lupus Erythematosus - Erika Yusticia Handayani; Ligat Pribadi Sembiring (Sean Institute, 2024)
Glomerulonephritis (GN) is a heterogeneous disorder characterized by glomerular compartment damage of the nephron mediated by autoimmunity. Secondary GN can occur for the patients with systemic autoimmune disease and has higher prevalence of peripheral artery disease. Symptoms and signs of GN are characterized by periorbital oedema accompanied by leg oedema, massive proteinuria, decreased renal function, hypertension, hematuria and erythrocyte casts. We reported a 40 years old female patient found with anasarca oedema, pain in the right foot, and proteinuria who had a history of systemic lupus erythematosus for 7 years. On physical examination, we found hypertensive urgency, anasarca oedem and blackish ulcus on the dorsal pedis extremity dextra. Laboratory data showed hypoalbuminemia, hypernatremia, creatinine clearance 19.38 ml/min, and albumin creatinine ratio 18.949 mg albumin/gr cr, ANA profile arthritis + 4.2. Urynalysis showed massive proteinuria, erythrocytes and casts were present. CT angiography showed the impression of peripheral artery disease.